Draft Annual Plan (1995-96) Government of Goa Part-II-C Plan Proposals in Detail of (Sectors) - Planning Commission (Planning Commission, 1995)
In keeping pace with the National Policy on Education the thrust on Elementary education will be to Education two aspects Viz. (1) Universal enrolment and retention of children upto 14 years of age and (ii) a substantial improvement in the quality of Education. During the first three years of the VIIIth Plan 1992-97 anticipated expenditure will be Rs. 1275.53 lakhs i.e. 48.69% of the VIIIth Plan Outlay and 35.6 % of the targeted amount.
Government of Goa, Directorate of Planning, Statistics and Evaluation